2015
DOI: 10.1128/genomea.00575-15
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Anoxybacillus geothermalis Strain GSsed3, a Novel Thermophilic Endospore-Forming Species

Abstract: Anoxybacillus geothermalis strain GSsed3 is an endospore-forming thermophilic bacterium isolated from filter deposits in a geothermal site. This novel species has a larger genome size (7.2 Mb) than that of any other Anoxybacillus species, and it possesses genes that support its phenotypic metabolic characterization and suggest an intriguing link to metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…And positive result to A. mongoliensis sample Seq10 and A. kestanboliensis sample Seq18. The result of this study agree with the concept previously reported by Filippidou et al, (2015) who found urease enzyme positive for A. geothermalis Strain GSsed3.…”
Section: Discussionsupporting
confidence: 93%
“…And positive result to A. mongoliensis sample Seq10 and A. kestanboliensis sample Seq18. The result of this study agree with the concept previously reported by Filippidou et al, (2015) who found urease enzyme positive for A. geothermalis Strain GSsed3.…”
Section: Discussionsupporting
confidence: 93%
“…Genome sequence and annotation of this strain has been submitted to Genbank under accession number YCG00000000.1 (Filippidou et al, 2015). The DNA G+C content of GSsed3 T was slightly higher than the values reported for the reference strains (Table 1).…”
Section: Anoxybacillus Bogrovensis Dsm 17956 T (Am409184)mentioning
confidence: 92%
“…Screening of phylogenetic neighbours of strain GSsed3 T was carried out using EzTaxon-e (Kim et al, 2012), taking into account 16S rRNA gene sequences from cultured isolates. Sequences of all species of the genus Anoxybacillus along with Aeribacillus pallidus strain GS3372 (Filippidou et al, 2015), as an outgroup, were obtained and used to build phylogenetic trees using the online tools of the phylogeny.fr website (Dereeper et al, 2008). The tree topology was verified using four independent methods for the reconstruction of phylogenetic trees, neighbour-joining, maximum-likelihood, maximum-parsimony and Bayesian inference (Anisimova & Gascuel, 2006;Castresana, 2000;Dereeper et al, 2008;Elias & Lagergren, 2007;Gascuel, 1997;Goboloff et al, 2000;Guindon et al, 2010;Huelsenbeck & Ronquist, 2001;Ronquist & Huelsenbeck, 2003).…”
mentioning
confidence: 99%
“… The reference protein sequence is denoted as 100%. AB04: A. ayderensis AB04 [ 5 ]; AF/04: A. thermarum AF/04 [ 42 ]; BAA-2555: Anoxybacillus geothermalis [ 43 ]; BCO1: Anoxybacillus sp. BCO1 [ 44 ]; DSM15939: Anoxybacillus amylolyticus DSM15939 [ 42 ]; DSM27374: Anoxybacillus suryakundensis strain DSM 27374 [ 45 ]; G2: A. gonensis G2 [ 32 ]; G10: A .…”
Section: Figurementioning
confidence: 99%